Magic, emotions and film producers: unlocking the “black-box” of film production - Ostrowska, Dorota (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2013)
The starting point in the article is production culture research. Dorota Ostrowska points that – contradictiory to promises – this approach still failed to provide analisis showing connection between production culture and textual characteristic of particular films. She mentions a few successful research endevours aimed to highlight that connection such as Wisconsin researches classical Hollywood cinema examining. Then Ostrowska proposes Flusser’s reflections and Action-Network Theory as promising theoretical backgrounds for production culture research. In conclusion she points also the persepctive originated in organisational science (subdivision of management studies) as a worthy tool to aplication in film production studies. This approaches is based on close examining of organization also in emotional and sensual terms. Ostrowska argues that emotional dimension of cinema, which is traditionally highlightened, could be also connected with production process and work of film crews.
Keywords: production studies; Action-Network theory; organisational science; emotions in organizations